PRODUCT UNIQUENESS VALUE ADVANTAGE TO IMPROVE MARKETING PERFORMANCE - Khasanah, Imroatul; Astuti, Sri Rahayu Tri (Universitas Muria Kudus, 2025)
This study investigates how product uniqueness value advantage mediates the relationship between product innovation and marketing performance. Data were gathered from 342 food-producing SMEs in Central Java, Indonesia. The owners and managers of food product SMEs in Central Java are the respondents of this study's survey. Data collection was conducted over a three-month period using structured questionnaires distributed directly and supplemented by interviews. The research model includes five assumptions that were investigated using Structural Equation Modelling (SEM). Product innovation, product uniqueness value advantage, long-term competitive advantage, and marketing performance were the variables studied. The findings suggest that all hypotheses have a favorable and significant effect. Among these, product uniqueness value advantage has the greatest influence on marketing performance. Several recommendations are suggested to utilize this advantage and thus boost marketing performance: SMEs should: actively and quickly create new product variations for the market; be creative in creating food products that showcase unique qualities that suit consumer tastes; (3) strive to be leaders in launching new product concepts; and (4) be flexible and responsive to changing market trends, especially when it comes to adjusting to the food industry's explosive growth. The findings of this study have several limitations that must be addressed in future research. The impact of sustainable competitive advantage on marketing success is minimal compared to the influence of other variables. To better understand its impact on marketing performance, future research could examine increasing the number of indicators for the sustainable competitive advantage variable to provide a more comprehensive measure of this concept.